Tracing the Spiral Structure of the Outer Milky Way with Dense Atomic Hydrogen Gas. (21st July 2017) - Koo, Bon-Chul; Park, Geumsook; Kim, Woong-Tae; Lee, Myung Gyoon; Balser, Dana S.; Wenger, Trey V.
Abstract: We present a new face-on map of dense neutral atomic hydrogen ( H i ) gas in the outer Galaxy. Our map has been produced from the Leiden/Argentine/Bonn H i 21 cm line all-sky survey by finding intensity maxima along every line of sight and then by projecting them on the Galactic plane. The resulting face-on map strikingly reveals the complex spiral structure beyond the solar circle, which is characterized by a mixture of distinct long arcs of H i concentrations and numerous "interarm" features. The comparison with more conventional spiral tracers confirms the nature of those long arc structures as spiral arms. Our map shows that the H i spiral structure in the outer Galaxy is well described by a four-arm spiral model (pitch angle of 12 ° ) with some deviations, and gives a new insight into identifying H i features associated with individual arms.